Exploring the Entrepreneurial Mindset: The Impact of Innovation, Proactiveness, and Risk-Taking on ITBSS Students Entrepreneurial Interest - Vinsensius; Ryandra, Calvin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Sabda Setia, 2024)
This research investigates the relationship between entrepreneurial mindset and entrepreneurial intention, focusing on the role of innovation, proactiveness, and risk taking. The aim of this research is to explore how these factors influence entrepreneurial intentions among students, especially at the Institut Teknologi dan Bisnis Sabda Setia (ITBSS). The method used in this research is a quantitative approach, which includes data collection through questionnaires and interviews. The research results show that there is a positive correlation between entrepreneurial thinking patterns and entrepreneurial intentions. The entrepreneurial mindset consists of five main dimensions: opportunity orientation, innovation, proactiveness, self-confidence, and risk taking. The conclusion of this research confirms that students with a strong entrepreneurial thinking pattern tend to have higher entrepreneurial intentions. This research does not discuss business success in detail, but emphasizes the importance of the relationship between entrepreneurial thinking patterns and entrepreneurial intentions.